Theodore Roethke’s “The Far Field”: The Spiritual Experiences through Jungian Archetypes: Theodore Roethke’s “The Far Field”: The Spiritual Experiences through Jungian Archetypes - Almohammed, Hala; Mahmoud , Amel (Humanities Journal of University of Zakho, 2022)
ABSTRACT: This research paper deals with one of the most prominent poems by a modern American poet Theodore Huebner Roethke (1908-1963) and the title of the poem is “The Far Field” (1964). The current paper examines the underlining mystical significance of the images used in Roethke’s “The Far Field.” In this poem, the poet figuratively expresses his spiritual journey to realize God within himself through deep contemplation in nature. Very much similar to the mystic experience of realizing the divine within himself while living in solitude. The discussion explores particular Jungian archetypes in this poem scrutinizing their referentiality both on the aesthetic figurative level of the poem and on the spiritual dimension. For example, Roethke dexterously employs the image of the far field to refer to death but interestingly this far field with which dead animals are strewn about is also a symbol of rebirth where new life is destined to emerge like a garden that decays in September only to flourish back in spring. Thereby, throughout such images drawn from nature, the poet portrays the different stages of spiritual growth he passes through. These stages are; fear of mortality, transcending this fear through realizing the cycle of birth and death which is the reincarnation, and finally the detachment from the physical realism into a union with the divine.